Don Hamrick puts light bulb back into the fixture after it stopped burning, but later worked, 1964. - (:unkn) unknown (Forsyth County Public Library, 2008)
WSJ 1-26-64 p. A3.
Don Hamrick puts light bulb back into the fixture after it stopped burning, but later worked, 1964.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth